SATISFACTION WITH WORKING CONDITIONS OF EMPLOYEES IN RESTAURANTS IN NOVI SAD - Šmugović, Stefan; Kalenjuk, Bojana M; Grubor, Biljana (The Business of Tourism, 2020)
Employee satisfaction is one of the key conditions for the success of a company. In order for an organization to succeed in business, it must know its employees and align their individual goals with organizational goals. Catering, as an expanding activity, is characterized by a large turnover of employees, which makes finding and retaining quality staff a very serious task for the organization. In order to increase their chances and keep competent staff, organizations must take care of the satisfaction of their employees. The aim of this research is to determine the degree to which restaurants in Novi Sad care about the satisfaction of their employees and whether the type of restaurant determines the degree of their satisfaction.
Keywords: satisfaction; working conditions; employees; restaurant; Novi Sad